Smart energy meter with adaptive communication data transfer algorithm for electrical energy monitoring - Ab Halim, Haizum Hanim (2021)
Smart Meter (SM) is an intelligent device with additional functions which include the ability to measure and record energy consumptions, and allows two-way communication with the utility for automated monitoring, and accurate billing management. Smart metering program has gained importance and started to be implemented in most developed country including Malaysia. The obvious problem in this SM is it uses single communication system as there was no contingency plan in transferring the data when the signal strength was weak or failure during data transfer process. In addition, single communication on the smart meter has limiting the location suitability of the meter. Thus, in this thesis, a new Smart Energy Meter (SEM) with adaptive data transfer algorithm is designed to accommodate the problem. The prototype of SEM is constructed based on the modern Smart Meter design and modified with additional control devices and sensors, so that it can measure, record and transfer the data using designated algorithm combining three types of communication system in one device; Wi-Fi, GSM and RF. The idea of combining three types of wireless communication is to ensure the data fully transferred to the data center accurately and promptly. The prototype is constructed through software and hardware development and has been programmed using Arduino IDE software. An algorithm for selecting communication system is developed by comparing Received Signal Strength Indicator (RSSI) of Wi-Fi and GSM with the priority given to Wi-Fi, followed by GSM and RF. The prototype has been tested on a laboratory scale for its functionality by measuring the electrical parameters using heating elements as the load, and its ability in transferring data through three communications and monitoring as well as communicating with the SEM from DIS. Index test on the algorithm performance is carried out at different locations and atmospheric for example in an indoor area of KEE 009 laboratory (normal weather), the outdoor area of KEE 009 laboratory in normal weather, multi storey building and during thunderstorm weather. In a conclusion, SEM prototype and adaptive communication data transfer algorithm with a combination of the three communication will be another method to solve a single communication problem of SM and suitable in residential location that offered the proposed communication infrastructure.